Pediatric and adolescent injury in snowboarding - Russell, K.; Selci, E. (Research in Sports Medicine, 2018)
To systematically review published literature on pediatric snowboard injuries, a literature search was performed in PubMed for "snowboard*". Studies must 1) have been primary research; 2) included at least 10 snowboarders; 3) included children and/or adolescents 4) reported specific injury outcomes, risk factors, or injury prevention program effectiveness. The overall injury rates ranged from 0.5 per 1,000 runs to 420 per 1,000 snowboarders. The most common injuries types were fractures, sprains and strains. Most injuries occurred to an upper extremity or the head. Falls and collisions were the most common mechanisms. Snowboarders who were younger, female, had less snowboard experience, or had a previous injury were at greater risk for injury. Wearing wrist guards had a protective effect. Injury rates varied by injury denominator and source of data. Injury prevention efforts should evaluate modifiable extrinsic risk factors, such as strategies to increase use of protective equipment.